(untitled) (Journal of the College of Basic Education, 2022)
This topic deals with the Kufic opinions mentioned by the author of the book Al-Insaf, that the Basrans have gone to them, and as it will appear through this research, that the Kufans are the ones who were influenced by the Basrans and their opinions, and not the other way around. And they put it in their style and put frameworks for it and attributed it to themselves.